2017
DOI: 10.1007/s10815-017-1076-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex selection for non-medical indications: a survey of current pre-implantation genetic screening practices among U.S. ART clinics

Abstract: The majority of U.S. ART clinics offer non-medical sex selection, a percentage that has increased substantially since last reported in 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…27 A survey conducted in the USA found that 72.7% of ART clinics in the USA offer gender selection to their patients. 28 Although PGT for gender selection is illegal in the UK and the vast majority of European countries, clinics in the USA have reported a significant surge in fertility patients from countries such as the UK, Europe and Australia. 29 Despite the controversy and debate surrounding sex selection, surprisingly very few studies have investigated the motivations and attitudes of the patients using or potentially using this option.…”
Section: Key Messagementioning
confidence: 99%
“…27 A survey conducted in the USA found that 72.7% of ART clinics in the USA offer gender selection to their patients. 28 Although PGT for gender selection is illegal in the UK and the vast majority of European countries, clinics in the USA have reported a significant surge in fertility patients from countries such as the UK, Europe and Australia. 29 Despite the controversy and debate surrounding sex selection, surprisingly very few studies have investigated the motivations and attitudes of the patients using or potentially using this option.…”
Section: Key Messagementioning
confidence: 99%
“…Regulation around sex‐selection for non‐medical reasons varies based on jurisdiction. The use of technologies such as sperm‐sorting and pre‐implantation genetic diagnosis is an established practice in regions where pre‐conception non‐medical sex‐selection is permitted. There is less evidence for the use of TOP as a method of sex‐selection for family balancing.…”
Section: Sex‐selection: Current Practice and Motivationsmentioning
confidence: 99%
“…PGD (now called PGT-M; pre-implantation genetic testing for monogenic/single gene diseases) and sex selection are not allowed in many European countries, including the UK and Germany, except for screening of genetic and inherited disorders. Worldwide, the major destination for unrestricted PGD and sex selection is the USA [57].…”
Section: Pre-implantation Genetic Diagnosis and Sex Selectionmentioning
confidence: 99%